High-resolution ultrasound study of morphological changes of the pylorus in the postoperative cases of infantile hypertrophic pyloric stenosis - Mriganka Guria; Dipak Ghosh; Janki Bisth; Swadha Priya Basu; Kaushik Saha (Wolters Kluwer Medknow Publications, 2021)
Aims: The aim of this study was to find & compare the pyloric Canal Length (CL), Pyloric muscle thickness (MT) by using the High Resolution Ultrasonography (HRUS) in Preoperative & postoperative period (after Ramstedt Pyloromyotomy) for Infantile Hypertrophic Pyloric Stenosis (IHPS). Methods: From January 2018 to June 2019, we have performed HRUS for 40 patients of clinically diagnosed cases of IHPS. & Ultrasonography machine: Phillips HD 7 machine & Alpinion E-CUBE with 3-12MHz linear probe, 3.5-5 MHz curvilinear probe and 5-7.5 MHz sector probe were used. The sonographic criteria for positive IHPS are Pyloric muscle thickness (MT) > 3 mm, pyloric Canal length (CL) >14 mm. Postoperative MT & CL at 2 month, 4 month & 6 month were determined and results were analysed with the preoperative pyloric parameters. Statistical analysis used: Mean and standard deviation of values were obtained by using Microsoft excel and statistical significance was analysed by regression study of grouped variables showing p - value by Microsoft excel. Results: Pyloric parameters (MT & CL ) gradually attain normal values over months and 80 % of patients showed resolution of pyloric MT & CL values by 6 months. MT assessment shows statistical significance at six months scan ( p- value <0.05). Conclusions: Serial postoperative HRUS in IHPS cases show gradual ( mostly by 6 months) resolution of pyloric parameters ( MT & CL ) to normal. MT appears to be a consistent parameter for serial assessment.